2018
DOI: 10.1021/acs.molpharmaceut.8b00014
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine A-Loaded Nanocarriers for Topical Treatment of Murine Experimental Autoimmune Uveoretinitis

Abstract: In the present study, tissue distribution and the therapeutic effect of topically applied cyclosporine A (CsA)-loaded methoxy-poly(ethylene-glycol)-hexyl substituted poly(lactic acid) (mPEGhexPLA) nanocarriers (ApidSOL) on experimental autoimmune uveitis (EAU) were investigated. The CsA-loaded mPEGhexPLA nanocarrier was tolerated well locally and showed no signs of immediate toxicity after repeated topical application in mice with EAU. Upon unilateral CsA treatment, CsA accumulated predominantly in the corneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Animal models are essential tools to help develop and validate new drugs. So far, proteasome inhibitor ( 42 ), immunosuppressant-loaded nanoparticles ( 43 ), and gut microbial metabolites ( 6 ) have been applied on murine uveitis models. In this study, we successfully validated the anti-inflammatory effect of prednisone on zebrafish EIU model, suggesting this model as an effective tool for future drug screening studies.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models are essential tools to help develop and validate new drugs. So far, proteasome inhibitor ( 42 ), immunosuppressant-loaded nanoparticles ( 43 ), and gut microbial metabolites ( 6 ) have been applied on murine uveitis models. In this study, we successfully validated the anti-inflammatory effect of prednisone on zebrafish EIU model, suggesting this model as an effective tool for future drug screening studies.…”
Section: Discussionmentioning
confidence: 99%
“…This treatment regimen led to a reduction in EAU severity in the treated eyes when compared to control eyes treated with PBS. This improvement was associated with a decrease in T-cell count, T-cell proliferation, and IL-2 secretion from cells in the LN on the same side . Unfortunately, despite all the positive in vitro and preclinical studies outcome of CyA-loaded mPEG-hexPLA micellar formulation (ApidSOL), no further preclinical/clinical progress has been reported since this 2018 study.…”
Section: Topical Delivery By Micellar Formulations To the Eyementioning
confidence: 95%
“…110 In 2018, Kasper et al conducted tissue distribution and efficacy studies for a CyA-loaded mPEG-hexPLA micellar formulation (ApidSOL) in a B10.RIII mouse model of experimental autoimmune uveitis (EAU). 107 They found that the topically administered CyA-loaded mPEG-hexPLA micelles were well-tolerated and did not exhibit any immediate toxicity when applied repeatedly on mice EAU. After using the CyA treatment on one eye, the drug primarily accumulated in the corneal and sclerachoroidal tissues of the treated eye as well as in the lymph nodes.…”
Section: Micelles Based On Diblock Copolymers For Ocular Drug Deliver...mentioning
confidence: 99%
“…Micelle formulations (i.e., PEG-PCL, PEG-PLA, PEG-PLGA, HS 15) are not innovative in structure, which have been improved in ocular application, making various data improved including drug loading rate, corneal penetration, safety, and stability significantly compared with previous traditional preparations or current commercial preparations. [41][42][43][46][47][48] For example, two optimal formulations (B58-Transcutol® P under the 20:1 ratio of HS 15: drug; B58-propylglycol under the 20:1 ratio of HS 15: drug.) were developed to improve the solubility of STZ by nearly 339 times.…”
Section: Advances Of Polymeric Micellesmentioning
confidence: 99%
“…For example, Kasper et al prepared a methoxy-poly(ethylene-glycol)–hexyl iodide poly(lactic acid) (mPEGhexPLA) nanomicelle for delivery of cyclosporine A (CsA) in the treatment of uveitis. 41 Calcineurin inhibitor CsA is not only poor in water solubility, but also organotoxic. This unique mPEGhexPLA polymeric micelle could address the problems of drug insolubility, low bioavailability, and toxicity.…”
Section: Polymeric Micelles That Act Directly As the Delivery Vectormentioning
confidence: 99%